1997
DOI: 10.1542/peds.99.3.e1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Recurrent Otitis Media Among Children in the United States

Abstract: ABSTRACT. Background. The number of visits for otitis media, the most common diagnosis among preschool children, has increased during the past decade. This study was undertaken to determine whether there has been a concurrent increase in the prevalence of recurrent otitis media among children in the United States and to identify risk factors or demographic changes to explain the increase.Methods. Although the prevalence of recurrent otitis increased with age, the greatest increase in recurrent otitis media occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
110
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 24 publications
11
110
1
1
Order By: Relevance
“…However, because some of the signs/symptoms diagnostic for AOM overlap those for a cold-like illness (CLI) which is most often the appreciable expression of a viral upper respiratory tract infection (vURI) and a known precipitant of OM 10-13 , clinical certainty with respect to assignment to this subcategory is undermined. Also, many studies of AOM incidence abstracted the reported presentations from large data bases representing multiple health care providers [14][15][16][17] , and given the variable the skills of the contributing physicians 18 , the quality of those data is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…However, because some of the signs/symptoms diagnostic for AOM overlap those for a cold-like illness (CLI) which is most often the appreciable expression of a viral upper respiratory tract infection (vURI) and a known precipitant of OM 10-13 , clinical certainty with respect to assignment to this subcategory is undermined. Also, many studies of AOM incidence abstracted the reported presentations from large data bases representing multiple health care providers [14][15][16][17] , and given the variable the skills of the contributing physicians 18 , the quality of those data is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…20 -24 Observations on whether there are racial differences in the prevalence of OM vary. Although clinic-based research and survey data from national samples indicated that black children were less likely than white children to have either acute OM or FEI, 13,[21][22][23] other researchers, using active surveillance, monthly study visits, and objective diagnostic criteria, found similar rates of OM during the first 2 years of life. 4,25 They speculated that racial disparities observed in other studies may be attributable to differential access to health care, differential rates of detecting OM, or both.…”
mentioning
confidence: 97%
“…The decreased frequency of acute mastoiditis has been ascribed to antibiotics, but improvements in social conditions, in particular housing and nutrition, are key elements whose contributions remain unclear. In the USA there are concerns regarding possible increases in recurrent otitis media 9 and mastoiditis 10 ; however, for the Birmingham Children's Hospital (serving a population of about one million children within the West Midlands) the number of cases of mastoiditis remained unchanged between 1993 and 1998 at roughly 6 per annum.…”
Section: J O U R N a L O F T H E R O Y A L S O C I E T Y O F M E D I mentioning
confidence: 99%